2020
DOI: 10.5455/jpma.45424
|View full text |Cite
|
Sign up to set email alerts
|

Non-Recurrent Laryngeal nerve: A case report and review of literature

Abstract: Right recurrent laryngeal nerve can take a "Non-Recurrent" course and can present as a Non Recurrent Laryngeal nerve which is a rare entity. Such anomalies can lead to difficulty in locating the laryngeal nerve during thyroid surgeries and there are higher chances of it being injured. Therefore, surgeons should be mindful of this entity. We report the case of a 53-year-old lady who underwent thyroid surgery and a right Non Recurrent Laryngeal Nerve was identified intra-operatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 7 publications
0
5
0
3
Order By: Relevance
“…The main reasons for the low endorsement of case reporting guidelines are the emerging case report formats and the lack of knowledge of editors about the existence of these guidelines. [ 5 ] In this study, 27 new types of case report were identified. The purpose of changing the format of reports in the educational objectives section is to increase the knowledge of fellowship students and novice clinicians.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The main reasons for the low endorsement of case reporting guidelines are the emerging case report formats and the lack of knowledge of editors about the existence of these guidelines. [ 5 ] In this study, 27 new types of case report were identified. The purpose of changing the format of reports in the educational objectives section is to increase the knowledge of fellowship students and novice clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 4 ] Now, it seems that each journal has special processes for publishing case reports and no uniform guideline is available. [ 3 5 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also have the potential to guide future research. [1][2][3][4] There is widespread agreement that research and reporting guidelines are essential for enhancing the quality of the healthcare literature. 5 Reporting guidelines are intended to assist authors by enhancing the completeness, transparency, and accuracy of their reports, thus decreasing the volume of inadequately written manuscripts submitted to scientific journals.…”
Section: Introductionmentioning
confidence: 99%
“…Although often considered low‐quality evidence, case reports can provide information that can be subsequently applied in clinical practice, as well as data on the therapeutic efficacy, adverse effects, and costs of interventions. They also have the potential to guide future research 1–4 …”
Section: Introductionmentioning
confidence: 99%